2019
DOI: 10.1111/aos.14280
|View full text |Cite
|
Sign up to set email alerts
|

The association study of lipid metabolism gene polymorphisms withAMDidentifies a protective role forAPOE‐E2 allele in the wet form in a Northern Spanish population

Abstract: Purpose: To elucidate the potential role of eleven single nucleotide polymorphisms (SNPs) in the most relevant lipid metabolism genes in Northern Spanish patients with age-related macular degeneration (AMD). Methods: A case-control study of 228 unrelated native Northern Spanish patients diagnosed with AMD (73 dry and 155 wet) and 95 healthy controls was performed. DNA was isolated from peripheral blood and genotyped for the SNPs APOE rs429358 and rs7412; CTEP rs3764261; LIPC rs10468017 and rs493258; LPL rs1267… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
10
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 9 publications
(10 citation statements)
references
References 99 publications
0
10
0
Order By: Relevance
“…40 In recent years, the roles of inflammation and lipid metabolism in retinal diseases have been highlighted. [41][42][43] This review mainly focused on the regulation of inflammation by LCPUFA metabolism to facilitate drug development and clinical research.…”
mentioning
confidence: 99%
“…40 In recent years, the roles of inflammation and lipid metabolism in retinal diseases have been highlighted. [41][42][43] This review mainly focused on the regulation of inflammation by LCPUFA metabolism to facilitate drug development and clinical research.…”
mentioning
confidence: 99%
“…Particularities of the Brazilian population, including a great miscegenation and ethnic heterogeneity, increase the interest regarding the genetic profile of AMD and its relationship with data described in the literature in other populations. The only Brazilian study available in the literature 25 did not demonstrate a significant association between APOE polymorphisms and AMD risk. These results may be related to the sample size, which included 134 cases and 164 controls.…”
Section: Discussionmentioning
confidence: 80%
“…Schmidt et al 28 and Adams et al 29 also related the E2 and AMD association with smoking status. A recent study 25 described, for the first time, a protective effect for the E2 allele in relation to wet AMD in a Spanish population (OR 0.42; 95% CI 0.19-0.95).…”
Section: Discussionmentioning
confidence: 96%
See 1 more Smart Citation
“…Multiple studies have shown that there is a strong correlation between multiple genetic variants in this gene cluster and AMD (Johnson et al, 2001). Recently, it has been discovered that the apolipoprotein E (APOE) gene has a strong correlation with AMD (Fernández-Vega et al, 2020). The APOE gene plays a role in transporting lipids and cholesterol in the central nervous system, and multiple studies have shown that this gene is associated with neurodegenerative diseases such as Alzheimer's disease and stroke (Feher et al, 2006;Zhao et al, 2019Zhao et al, , 2020d.…”
Section: Introductionmentioning
confidence: 99%